2016
DOI: 10.1007/s11356-016-6442-6
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and temporal trends of farmland soil PBDEs: processes and crop rotation effects

Abstract: The concentration and temporal trend of PBDEs in farmland soil during a circle of crop rotation period within an e-waste dismantling area of South China were investigated. The averaged current concentration of total PBDEs in the farmland soil was averaged 19.1 ± 20.7 ng/g dry weight, which was much lower than the PBDE level in roadside soil and in topsoil near e-waste dismantling sites. Spatial distribution of total PBDEs concentration in the study area showed higher level at the field near e-waste workshops a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 33 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…The transfer of PBDEs to these locations has strong implications regarding human exposure via soil ingestion and the contamination of private land. Emission of BFRs to agricultural and residential soils has been repeatedly observed in e-waste recycling regions of China. ,, Although soil concentrations have not been assessed near formal e-waste facilities outside China, elevated atmospheric BFR concentrations have been observed at formal plants in Finland, U.S., Sweden and a large automotive shredding and metal recycling plant in the City of Brisbane, Australia . Processing of electronic waste was found to cause greater atmospheric emission of BFRs than landfill or incineration in Norwegian waste facilities, which supports the hypothesis that e-waste facilities are responsible for greater levels of contamination in Melbourne than other previously identified point-sources. , …”
Section: Resultsmentioning
confidence: 70%
“…The transfer of PBDEs to these locations has strong implications regarding human exposure via soil ingestion and the contamination of private land. Emission of BFRs to agricultural and residential soils has been repeatedly observed in e-waste recycling regions of China. ,, Although soil concentrations have not been assessed near formal e-waste facilities outside China, elevated atmospheric BFR concentrations have been observed at formal plants in Finland, U.S., Sweden and a large automotive shredding and metal recycling plant in the City of Brisbane, Australia . Processing of electronic waste was found to cause greater atmospheric emission of BFRs than landfill or incineration in Norwegian waste facilities, which supports the hypothesis that e-waste facilities are responsible for greater levels of contamination in Melbourne than other previously identified point-sources. , …”
Section: Resultsmentioning
confidence: 70%
“…It is striking that no PBDEs were detected in any of the farms, because they are described in the literature as frequent contaminants of agricultural soil [ 56 , 57 , 58 ]; however, it is true that the reported concentrations are mainly related to the use of treated wastewater [ 57 ], or to highly industrialized countries [ 58 ]. Previous studies have shown that the rate of flame retardant contamination in the Canary Islands is relatively low [ 17 , 18 , 38 ], which has been related to the relatively low industrial activity in this region [ 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%